ESP ISSUE IN INDONESIAN TERTIARY CONTEXT: WHAT STUDENTS NEED IN LEARNING ENGLISH - Gestanti, Rohfin Andria; Nimasari, Elok Putri; Mufanti, Restu (PUPIL: International Journal of Teaching, Education and Learning, 2019)
This study aims to analyze students’ English needs in an ESP course. English for specific purposes has become a significant aspect in the learning process in Indonesian tertiary context. The significant of occupation requirement globally and the emergence of mastering certain skills for certain jobs drives the need of English for specific area. Referring to this concern, General English is considered no longer suitable and it should be specified into several subjects based on certain purposes. In this case, ESP gives chances for students and teacher to define the target or the outcomes based on their purposes by considering their needs. Thus, conducting need analysis is the first, most significant part to be conducted in ESP course. Conducted in a private university in Indonesia, this study employed descriptive qualitative approach that used questionnaire and focus group discussion to collect the data. This study is a representation of teaching reflection after conducting 6-month ESP class. The results showed that since the students are enrolled in Communication Science Department, they need material that encourages them to communicate and participate actively in the classroom, refers to their major and reflects occupation-oriented material. The materials that distinguish this subject from others emphasize the specification of ESP class and show that the material used cannot be generalized. Therefore, the teacher should consider these results to prepare for the next ESP course.